2017
DOI: 10.3329/jbcps.v35i2.33364
|View full text |Cite
|
Sign up to set email alerts
|

Post Operative Pulmonary Complications Following Surgery for Congenital Heart Disease

Abstract: Abstract:Objective: To identify the incidence and related factors for pulmonary complications and its impact on outcome in patients subjected to surgery for congenital heart disease (CHD). Conclusions: Pulmonary complications are common after surgery for CHD which is more common in small children and complex surgeries. It significantly affects outcome including duration of mechanical ventilation and length of stay but no effect in mortality. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The most frequent pulmonary consequence of cardiac surgery is atelectasis, seen on postoperative chest radiographs in approximately 50% to 90% of patients (Szelowski LA, et al Curr Probl Surg. 2015;52 [1]:531). In our study the incidence was found in atelectasis was 2.25%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most frequent pulmonary consequence of cardiac surgery is atelectasis, seen on postoperative chest radiographs in approximately 50% to 90% of patients (Szelowski LA, et al Curr Probl Surg. 2015;52 [1]:531). In our study the incidence was found in atelectasis was 2.25%.…”
Section: Discussionmentioning
confidence: 98%
“…Functional residual capacity (FRC) can decrease by up to 20% with anesthesia (Szelowski LA, et al Curr Probl Surg. 2015;52 [1]:531), and the thoracic manipulation and alteration of rib cage mechanics with a classic median sternotomy approach can lead to decreases in forced vital capacity (FVC) and expiratory volume in the first second of forced expiration (FEV1) that can last for months after surgery. Use of the cardiopulmonary bypass circuit can also lead to bronchoconstriction.4…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella, Pseudomonas and E. Coli were also found resistant to commonly used antibiotics. Hasan et al 18 There is an urgent need to address factors that are promoting antibiotic resistance in Bangladesh. Antibiotics can be purchased without a prescription in the country and many people use them to selftreat conditions such as dysentery, cold, cough and fever.…”
Section: Antibiotic Resistancementioning
confidence: 99%